Ruang Publik Pengarusutamaan Gender Dalam Kebijakan Adaptasi Perubahan Iklim Di Indonesia - Handayani, Dwi Wahyu (Jurnal Pendidikan Kewarganegaraan dan Politik, 2024)
The global water crisis, disaster-conflict linkages, and the impact of various crises on women's mental health and well-being require a gender-mainstreaming policy approach to climate change. The implementation of a gender mainstreaming approach requires a public space for women, as a space for autonomy to voice issues and produce policies that are in line with women's interests. This article examines how public space can be present in discussions on gender mainstreaming in climate change. This article aims to elaborate on the public sphere that will interpret gender mainstreaming of climate change. The method in this article uses library research, which collects data by understanding and studying theories from various literatures. The research results in the public sphere combining discursive democracy and complex problem-solving rationality, which is not centralized planning but an open society to realize policies. The discourse of gender mainstreaming can be utilized by women's groups whose knowledge capacity is improving through public space to discuss their interests related to climate change. The public space in Indonesia uses the development planning deliberation (musrenbang) from the local to the national level.